PHYTOCHEMICAL SCREENING OF SIJUKKOT EKSTRACT (Lactuca Indica L.) - Jesica C.R. Panjaitan; Albinus Silalahi (Indonesian Journal of Chemical Science and Technology (IJCST), 2020)
Have been carried out Phytochemical screening on Sijukkot  which determited as Lactuca indica L, the plant from Gibeon hill forrest area in the village of Parsaora Sibisa Ajibata, Toba Samosir, North Sumatera. Test carried out to determine the composition of secondary metabolites contained in these plants. It was started by extracting plant leaves using 96% ethanol solvent which was carried out by maceration method and concentrated using a rotary evaporator. The concentrated extract obtained was sponsored by phytochemical tests. Phytochemical test results on ethanol extracts from the leaves of the Sijukkot plant were obtained compositions namely Flavonoids, tannins, saponins, steroids and triterpenoids.